The Strategic Planning Formulation in Creative Industry Products Positioning in Sabang, Aceh - Utami, Sorayanti; Meldi Kesuma, Teuku; Siregar, M. Ridha; Halim, Hendra (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
Sabang City has been recognized as a creative city in the crafts subsector, particularly in producing and positioning creative industry products. This investigation delves into the strategic planning formulation utilized for the positioning of creative industrial products in Sabang. The examination utilizes a SWOT Analysis (examining Strengths, Weaknesses, Opportunities, and Threats), coupled with an Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE), to evaluate the strengths and weaknesses, as well as the opportunities and threats encountered by the creative industry in Sabang. The outcomes of the SWOT analysis provide valuable insights for reducing weaknesses, enhancing strengths, mitigating challenges, and capitalizing on opportunities in the strategic planning process. The findings of the study indicate that the advancement of positioning for creative economy products in Sabang falls within quadrant I, signifying Growth. Consequently, it employs the Strengths-Opportunities (SO) Strategy. By examining the strategic planning methods, this research aims to shed light on effective strategies that can be employed to position creative industry products successfully in Sabang.